Une vie marquée par le mépris - Caroline Protais; Maitena Milhet (Terrains/Théories)
This article presents the main results of a qualitative study carried out among people with different social stigmas (« drug addict », « mentally ill », « homeless », « delinquent »). It aims at qualifying their life experience and its consequences on identity. The recognition model of Axel Honneth is efficient to account for the social contempt experience that the respondents lived in intimacy but also in different social relegation worlds. The confrontation between our study and Honethian theory shows that different forms of contempt coexist in all scenes described by the interviewees. In addition, different forms of identity resistance can be identified. They nevertheless remain fragile.